NUT carcinoma: A rare presentation of a chest mass with hypercalcemia in a pediatric patient - Amanda K. Johnson; Travis Johnson; Katrina Winsnes; Jessica L. Davis (Elsevier, 2023)
The most common etiologies for chest masses in children include neurogenic tumors, germ cell tumors, leukemia/lymphoma and cysts [1]. Hypercalcemia of malignancy can complicate the clinical course, but is rare in children and most likely to occur in leukemia [2]. The following case illustrates a rare malignancy, NUT carcinoma, presenting as a mediastinal mass in a pediatric patient. The patient developed hypercalcemia, which further complicated the diagnosis. Due to the rapidly progressive nature of this malignancy as well as diagnostic challenges, the patient's malignancy was not formally diagnosed until post-mortem autopsy molecular testing. This report adds to the body of literature of this rare tumor to assist with diagnosis, management, and treatment for future patients.